PENGARUH PENGAWASAN KERJA DAN PENERAPAN PROGRAM KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS PEKERJA PROYEK KONSTRUKSI - Mohammad Djaelani; Eli Retnowati (Jurnal Ilmiah Satyagraha, 2022)
In general, the construction project development process contains anelement of danger in every operational activity. One of the focuses of the contractorcompany is to create good occupational health and safety conditions on the project.The performance of construction service companies can be improved by identifyingthe factors that influence the performance improvement and analyzing how muchinfluence these factors have on the company's performance. The purpose of thisstudy is to analyze and determine the effect of work supervision and theimplementation of occupational safety and health programs on the productivity ofconstruction project workers. The population is workers who work in constructionservice companies that are carrying out 18 construction projects, especiallyfacilities and infrastructure by a General Contractor, a company in Surabaya.Samples were taken as many as 100 workers. The results of the study prove to betrue that work supervision and the implementation of occupational safety andhealth programs determine the productivity of construction project workers.